Ex-vivo models of the Retinal Pigment Epithelium (RPE) in long-term culture faithfully recapitulate key structural and physiological features of native RPE. Issue 4 (August 2017) - Lynn, Savannah A.; Ward, Gareth; Keeling, Eloise; Scott, Jenny A.; Cree, Angela J.; Johnston, David A.; Page, Anton; Cuan-Urquizo, Enrique; Bhaskar, Atul; Grossel, Martin C.; Tumbarello, David A.; Newman, Tracey A.; et al.
Graphical abstract: Highlights: Damage to the Retinal Pigment Epithelium (RPE) is a key feature of retinopathy. We describe 2 substrates which support RPE cultures for long-term studies. Substrates were; a polyester transwell membrane and a novel electrospun scaffold. Both support RPE cultures with structural and functional features of native RPE. Electrospun scaffolds may be better for studying some disease-linked RPE changes. Abstract: The Retinal Pigment Epithelium (RPE) forms the primary site of pathology in several blinding retinopathies. RPE cultures are being continuously refined so that dynamic disease processes in this important monolayer can be faithfully studied outside the eye over longer periods. The RPE substrate, which mimics the supportive Bruch's membrane (BrM), plays a key role in determining how well in-vitro cultures recapitulate native RPE cells. Here, we evaluate how two different types of BrM substrates; (1) a commercially-available polyester transwell membrane, and (2) a novel electrospun scaffold developed in our laboratory, could support the generation of realistic RPE tissues in culture. Our findings reveal that both substrates were capable of supporting long-lasting RPE monolayers with structural and functional specialisations of in-situ RPE cells. These cultures were used to study autofluorescence and barrier formation, as well as activities such as outer-segment internalisation/trafficking and directional secretion of key proteins; the impairment of which underlies retinal disease. Hence, both substrates fulfilled important criteria for generating authentic in-vitro cultures and act as powerful tools to study RPE pathophysiology. However, RPE grown on electrospun scaffolds may be better suited to studying complex RPE-BrM interactions such as the formation of drusen-like deposits associated with early retinal disease.